War: The Ultimate Crime Against Humanity - Snyder, Sam (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
Review of Gwynne Dyer, War: the Lethal Custom (New York: Carroll & Graf Publishers, 2005).